(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This study investigates the impact of social factors on the evaluation of English slang within a sociolinguistic framework. Slang is examined as a dynamic and socially embedded linguistic phenomenon that reflects identity construction, group membership, and cultural change. The research explores how key social variables, including age, gender, social class, and educational background, shape attitudes toward slang and influence its perception across different communities. The study integrates theoretical perspectives from sociolinguistics, pragmatics, and discourse analysis, alongside empirical observations based on survey data. The findings indicate that the evaluation of slang is highly context-dependent and varies significantly among social groups. Younger speakers tend to associate slang with creativity and social belonging, whereas older and more formally educated individuals often perceive it as inappropriate in formal contexts. Additionally, the study highlights the role of language ideology, indexicality, and globalization in shaping the meanings and evaluations of slang. The results demonstrate that slang functions not only as an informal linguistic resource but also as a significant socio-cultural marker, contributing to the understanding of language variation and social interaction in contemporary English.